Modification of self-assembled monolayers by electron irradiation as a tool for surface engineering, lithography, and nanofabrication - Terfort, Andreas; Zharnikov, Michael (Advanced materials interfaces, 2025)
Self-assembled monolayers (SAMs) have long become an important element of modern nanotechnology. Apart from their primary use in tailoring the chemical and physical properties of surfaces and interfaces, they can be modified by physical tools, with electron irradiation being probably the most useful and versatile one. Here, the development and current state of this field is reviewed, addressing both fundamental aspects of this modification and the related implications and applications. Various types of SAMs, differing in their reaction to electron irradiation, are considered, and the impact of relevant factors affecting these reactions, such as the SAM quality, primary electron energy, and temperature, is analyzed. Based on this knowledge, the current applications of SAM engineering by electrons are introduced and discussed. These applications include tuning the SAM properties, preparation of binary SAMs, conventional and chemical lithography, fabrication of carbon nanomembranes (CNMs), enabling metal deposition onto SAMs, and design and fabrication of biointerfaces. Some of these applications, like chemical lithography and functional CNMs, are unique and can hardly be realized with any other technology. They hold significant potential for the future and will presumably soon make a transition from prototype laboratory experiments to real-life industrial applications.
Gesehen am 25.02.2026